تفريق العرف عن الإجماع وعمل أهل المدينة وأثره في صناعة الفتوى: Distinguishing custom (‘urf) from consensus (ijmā‘) and the practice of the people of Medina, and its impact on legal opinions (fatwas)." - Elbalazi, Samira Hasan; Mohamed Razi, Nor Fahimah; Abdul Khalil, Shahidra (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
ملخص البحث تتناول هذه الدراسة التفريق بين ثلاثة من الأدلة الشرعية، وهي: العرف، والإجماع، وعمل أهل المدينة، نظرًا لما بينها من تشابه في كونها تقوم على معنى الاتفاق، مما قد يؤدي إلى التباس في الفتوى ومستندها. وتهدف الدراسة إلى بيان الفروق بينها من حيث الحجية والمصدر والنطاق والثبات، مع إبراز دور العرف ومرونته في تنزيل الأحكام الثابتة بالإجماع وعمل أهل المدينة على الوقائع المتجددة. وقد اعتمدت الدراسة على المنهج الاستقرائي والتحليلي والمقارن، من خلال جانب نظري يُعنى بتحرير المفاهيم وبيان الفروق، وجانب تطبيقي يبرز أثر ذلك في عدد من المسائل الفقهية في أبواب متعددة. وتوصلت الدراسة إلى وجود تشابه بين هذه الأدلة من جهة، واختلاف بينها من جهة أخرى، حيث يستقل كل من الإجماع وعمل أهل المدينة بالحجية، بينما يقوم العرف بدور بياني وتقييدي لهما. كما تبين أن التفريق بين هذه المصادر يسهم في صناعة فتوى أكثر دقة في مستندها، ويحقق التوازن بين الثبات والمرونة في الأحكام الشرعية. ABSTRACT This study examines the distinction between three Islamic legal evidences: custom (‘urf), consensus (ijmā‘), and the practice of the people of Medina (‘amal ahl al-Madīnah), due to their similarity in representing a form of collective agreement, which may lead to confusion in legal reasoning and fatwā formulation. The study aims to clarify the differences between these evidences in terms of authority, source, scope, and stability, while highlighting the role of custom and its flexibility in applying rulings established by consensus and the practice of the people of Medina to contemporary and changing circumstances. The research adopts the inductive, analytical, and comparative methodologies through a theoretical part concerned with defining concepts and clarifying differences, and a practical part demonstrating their application in various jurisprudential issues across different chapters of Islamic law. The study concludes that although these evidences share certain similarities, they differ in their nature and legal authority. Consensus and the practice of the people of Medina are independent sources of legal proof, whereas custom serves as an explanatory and restrictive tool for them. The distinction among these sources contributes to producing more precise fatwā and achieves a balance between stability and adaptability in Islamic rulings.